Growth Response of Arctica Islandica to North Atlantic Oceanographic Conditions Since 1850 - Poitevin, Pierre; Thébault, Julien; Siebert, Valentin; Donnet, Sébastien; Archambault, Philippe; Doré, Justine; Chauvaud, Laurent; Lazure, Pascal (Frontiers in Marine Science, 2019)
The Northwest Atlantic is a key region with an essential role in global climate regulation, redistributing heat and influencing the carbon cycle. However, little is known about its variability before 1950, mainly because of the lack of long-term instrumental measurements. The hard parts of long-lived marine biota hold the potential to extend instrumentally derived observation by several decades or centuries and enhance our understanding of global climate processes. Here we investigate the effects of local, regional, and large-scale climate variability on the marine bivalve, Arctica islandica (Linnaeus 1767) from Saint-Pierre & Miquelon (SPM). This archipelago lies at the boundary zone between the cold Labrador Current in the north and the warm Gulf Stream waters to the south. This study presents the northernmost statistically robust A. islandica growth chronology (1850–2015) from the Western North Atlantic and its potential as an environmental proxy record for past climatic and hydrographic variabilities at different time and geographical scales. The chronology correlates significantly and positively with the Atlantic Multidecadal Oscillation (AMO; N=142, r=0.34, p<0.05) and negatively with the North Atlantic Oscillation (NAO; N=66, r=-0.36, p<0.05), two global climatic indices. The North Atlantic spatial pattern of correlation shows significant (p<0.05) and positive correlations of 0–100-m temperatures from 1950 with A. islandica growth in SPM encompassing the Sub-Polar Gyre area. These global-scale relationships are refined and the mechanisms leading to them explained by comparing A. islandica growth chronology to regional environmental datasets such as the Shelf Slope Front position, Tail of Grand Bank Transport, and Station 27 temperature and salinity. These relationships between the A. islandica shell growth record at SPM and environmental datasets covering different geographical scales yield details about SPM hydrodynamics. Moreover, these findings confirm the key role of this archipelago for studying large-scale hydrographic variability and ecosystem dynamics facing global changes.